FAKTOR PSIKOLOGIS PENYEBAB CERAI GUGAT DALAM KELUARGA MUSLIM MODERN: ANALISIS NORMATIF PUTUSAN DI PENGADILAN AGAMA AMUNTAI - Lailatus Shofa; Taufik Hidayat (PT. Sulthan Journal Publisher, 2025)
The phenomenon of divorce initiated by wives (cerai gugat) in modern Muslim families has shown a significant increase in Religious Courts, including the Amuntai Religious Court. Changes in husband–wife relationship patterns, dual role demands, and psychological dynamics within modern families often create tension between the ideal concept of marriage in Islam and the realities of domestic life. This study aims to analyze the psychological factors contributing to divorce lawsuits in modern Muslim families and to examine their relevance to the Islamic concept of marriage based on judicial decisions of the Amuntai Religious Court. This research employs a normative legal method with a case approach. Data were obtained through documentation studies of divorce lawsuit decisions Number 262/Pdt.G/2020/PA.Amt and Number 114/Pdt.G/2023/PA.Amt, which were analyzed using conceptual and statutory approaches within Islamic marital law. The results indicate that psychological factors such as prolonged disputes, lack of emotional responsibility, and mental and spiritual incompatibility between spouses constitute the dominant reasons for divorce lawsuits. These factors fulfill the element of continuous conflict as regulated in Islamic law. The study concludes that strengthening premarital education and incorporating Islamic family psychology approaches are essential preventive measures to reduce the rate of divorce lawsuits.